Implementation of Universal Banking for Financial Deepening Development in Indonesia - Prameshwari, Indira Indah (2008)
Nowadays, many developing countries are trying to develop financial deepening using various medium. One of the common medium to develop financial deepening is universal banking. Many developing countries apply universal banking into their financial system, with expectation this endeavour will give positive outcome to the country‟s financial and monetary condition. On the other hand, implementing universal banking is not an easy task. It requires enormous amount of time to implement universal banking with consideration of numerous aspects, and several issues might rises upon the implementation. In this dissertation, a qualitative-based research is employed using Indonesia as a scope of study for universal banking implementation in favour of financial deepening development. Several interviews have been conducted with some Indonesia‟s financial industry experts and regulators. Views from interviewees indicate that Indonesia should implement universal banking to strengthen its financial condition and financial stability. According to the interviewees, universal banking implementation will bring benefits to the Indonesia‟s financial system in the long run. Hence, this dissertation shows universal banking supports the process of the development of Indonesia‟s financial deepening.